2021
DOI: 10.1590/1984-0462/2021/39/2019180
|View full text |Cite
|
Sign up to set email alerts
|

Adverse Events Related to Mechanical Ventilation in a Pediatric Intensive Care Unit

Abstract: Objective: To identify the prevalence and factors associated with adverse events (AE) related to invasive mechanical ventilation in patients admitted to the Pediatric Intensive Care Unit (PICU) of a tertiary public hospital. Methods: This is a cross-sectional study from July 2016 to June 2018, with data collected throughout patients’ routine care in the unit by the care team. Demographic, clinical and ventilatory characteristics and adverse events were analysed. The logistic regression model was used for mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…However, invasive ventilation frequently has a high risk for subsequent complications, such as ventilator-associated pneumonia, airway stenosis, sepsis, acute respiratory distress syndrome, atelectasis, or pulmonary edema. [16][17][18] However, HFNC has recently gained rapid global adoption and became well documented in intensive and emergency health-care settings. 19,20 Several studies have indicated that HFNC is a simple, well-tolerated noninvasive respiratory support.…”
Section: Discussionmentioning
confidence: 99%
“…However, invasive ventilation frequently has a high risk for subsequent complications, such as ventilator-associated pneumonia, airway stenosis, sepsis, acute respiratory distress syndrome, atelectasis, or pulmonary edema. [16][17][18] However, HFNC has recently gained rapid global adoption and became well documented in intensive and emergency health-care settings. 19,20 Several studies have indicated that HFNC is a simple, well-tolerated noninvasive respiratory support.…”
Section: Discussionmentioning
confidence: 99%
“…Prolonged invasive mechanical ventilation may lead to laryngeal damage as pressure from the endotracheal tube is thought to cause ischemia and consequently erosion of the laryngeal mucosa. Young age, increased duration of endotracheal intubation and the use of cuffed tubes are associated with an increased risk of post-extubation stridor ( 30 , 31 ). Studies have not shown an association between the occurrence of stridor and the absence of an air leak prior to extubation, however, frequent endotracheal suctioning prior to extubation has shown to be a predictor for post-extubation stridor ( 32 ).…”
Section: Pediatric Complications Of Mechanical Ventilationmentioning
confidence: 99%
“…Unintended extubation (UE) is defined as any unintentional or unplanned dislodgement of an endotracheal tube (ETT) from the trachea (Table 1). 1,2 UE is the most common adverse event related to use of an artificial airway and can lead to complications including: hypoxemia and hypercarbia, hemodynamic compromise and arrest, need for emergent re‐intubation, and in rare cases death 3–5 . While reintubation in children does not carry the same mortality risks as adults, children who require reintubation have longer durations of mechanical ventilation and hospital stays, increasing their risk for nosocomial infections 6,7 .…”
Section: Introductionmentioning
confidence: 99%
“…1,2 UE is the most common adverse event related to use of an artificial airway and can lead to complications including: hypoxemia and hypercarbia, hemodynamic compromise and arrest, need for emergent re-intubation, and in rare cases death. [3][4][5] While reintubation in children does not carry the same mortality risks as adults, children who require reintubation have longer durations of mechanical ventilation and hospital stays, increasing their risk for nosocomial infections. 6,7 On average each paediatric UE increases total hospital cost by $36 000, and increases ICU and hospital length of stay by 5.5 and 6.5 days respectively, across age groups and diagnoses.…”
mentioning
confidence: 99%
See 1 more Smart Citation